META-ANALYSIS OF THE PREVALENCE OF OVERLAP BETWEEN BRONCHIAL ASTHMA AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) AMONG PATIENTS WITH BRONCHOPULMONARY PATHOLOGY - Raufov Alisher Anvarovich (Bright Mind Publishing, 2025)
Asthma and chronic obstructive pulmonary disease (COPD) are a major public health problem and represent a leading cause of morbidity and mortality worldwide [1,2]. Asthma and COPD are the most common chronic respiratory diseases worldwide, each with a specific pathophysiology [1]. Asthma is typically characterized by chronic airway inflammation with reversible symptoms, whereas COPD is characterized by persistent respiratory changes in the bronchopulmonary system [3,4However, patients may sometimes have clinical features of both diseases, a condition called asthma-COPD overlap (ACO), recommended by the joint GINA (Global Strategy for Asthma Management and Prevention) and GOLD (Global Initiative for Chronic Obstructive Lung Disease) guidelines. According to these guidelines, ACO is characterized by "persistent airflow limitation with some features of asthma and COPD."